Transcriptomic analysis and carbohydrate metabolism-related enzyme expression across different pH values in Rhizopus delemar - Liang, Jinpeng; Chen, Yulan; Li, Sisi; Liu, Dongyang; Tian, Hong; Xiang, Quanju; Zhao, Ke; Yu, Xiumei; Chen, Qiang; Fan, Hongzhu; Zhang, Lingzi; Penttinen, Petri; et al. (Frontiers in Microbiology, 2024)
Introduction: pH is one of the important factors affecting the growth and performance of microorganisms. Methods: We studied the pH response and plant growth-promoting (PGP) ability of Rhizopus delemar using cultivation experiments and transcriptomics, and verified the expression profiles using quantitative real-time PCR. Results: pH affected the growth and PGP properties of R. delemar. At pH 7, the growth rate of R. delemar was rapid, whereas pH 4 and 8 inhibited mycelial growth and PGP ability, respectively. In the pot experiment, the plant height was the highest at pH 7, 56 cm, and the lowest at pH 4 and pH 5, 46.6 cm and 47 cm, respectively. Enzyme activities were highest at pH 6 to pH 7. Enzyme activities were highest at pH 6 to pH 7. Among the 1629 differentially expressed genes (DEGs), 1033 genes were up-regulated and 596 were down-regulated. A total of 1623 DEGs were annotated to carbohydrate-active enzyme coding genes. Discussion: The PGP characteristics, e.g., phosphorus solibilization ability, of R. delemar were strongest at pH 7. The results provide useful information regarding the molecular mechanism of R. delemar pH response.